THE MORPHOSYNTACTIC AND LEXICAL-SEMANTIC ORGANIZATION OF THE TERMINOLOGY IN BRAZILIAN MARRIAGE CERTIFICATES: A DESCRIPTIVE STUDY - Barros, Lidia Almeida [UNESP]; Curti-Contessoto, Beatriz [UNESP] (Univ Estado Mato Grosso, 2019)
In this paper, we present a descriptive study on the morphosyntactic and lexical-semantic organization of the terms occurring in the field of Brazilian marriage certificates. For this, we based this research on the theoretical and methodological assumptions of Terminology (BARROS, 2004 e 2007; CABRE, 1999, among others). Concerning the methodology of our investigation, we identified the terminological unities recurrent in our corpus, composed of 333 Brazilian marriage certificates, with the aid of the Hyperbase program. Then, we analyzed it, which allowed us to describe this terminology regarding to its morphosyntactic and lexicalsemantic organization.
Keywords: Simple term; Syntagmatic term; Morphosyntactic and lexical-semantic organization; Marriage certificates